Analisis Fi’il Māḍī dalam Ayat Pendidikan Al-Qur’an dan Implikasinya bagi Mahasiswa PAI - Shafa Salsabila Yasmin; Rara Aprilia Syahputri; Tri Sundari; Salwa Amalia (CV. Jalan Cendikia, 2026)
The use of fiʿil māḍī in educational verses is essential for understanding how the Qur’an portrays the process of teaching, the endowment of intellectual potential, and the formation of human capabilities through language rich in meaning. The fiʿil māḍī form in these verses not only indicates past events but also emphasizes the certainty and perfection of divine actions in establishing the foundations of human education. This study employs a library research method, with data collection conducted through the analysis of Qur’anic exegesis literature, Arabic linguistic sources, scientific journal articles, and relevant academic documents. The findings reveal that the use of fiʿil māḍī in educational verses illustrates that teaching and the bestowal of intellectual and sensory faculties are divine decrees perfected by Allah since the very beginning of human creation. Furthermore, the implications for students of Islamic Religious Education (PAI) at INSAN Binjai are highly significant, particularly in fostering an awareness that the educational process is a spiritual trust that must be carried out with responsibility and integrity. Students are encouraged to emulate the systematic divine model of education, beginning with fundamental concepts, employing precise language, and orienting learning toward the development of learners’ potential. This understanding contributes to strengthening students’ pedagogical competence while simultaneously shaping the character of educators grounded in Qur’anic values.